GRICE’S COOPERATIVE PRINCIPLE VIOLATION IN THE SECOND PRESIDENTIAL DEBATE BETWEEN HILLARY CLINTON AND DONALD TRUMP - Lodari, Yoan; Kasmaini, Kasmaini; Sabarudin, Syafrizal (Journal of English Education and Teaching, 2018)
The aims of this research were to investigate kinds of maxims violated by the speakers and to investigate possible purposes of violations applied by the speakers. This research was conducted as qualitative descriptive study. The corpus of this research was Second Presidential transcript debate. The transcript was put into a checklist table and analyzed by Grice’s theory of Cooperative Principle. The results of this study showed that both Hillary Clinton and Donald Trump violated all maxims, with 75 violations by Hillary Clinton and 174 violations by Donald Trump. The most violated maxim by both speakers was maxim of quantity and the less violated maxim was maxim of manner. Moreover, the result showed the least possible purposes of violation by the speakers was to build positive political image towards hearer